A framework on improving integration of supply chain in Industrialised Building System (IBS) using design & build procurement in Malaysia / Ani Saifuza Abd Shukor - Abd Shukor, Ani Saifuza (Institute of Graduate Studies, UiTM, 2016)
The Malaysian Construction Industry Master Plan (CIMP 2006-2015) identified the innovative approaches of Industrialised Building Systems (IBS) and its supply chains as having important roles in improving productivity in construction processes. Supply chains in IBS involve relationships between many organisations and processes, with the evolution of specialised roles and embedded relationships. The procurement method is utilised as a mediator tool and as the means of controlling integration between players. A good supply chain integration practice leads to good integration among players. Although efforts exist to enhance IBS practice in Malaysia, establishing integration between IBS players is still a major hindrance. A framework for improving supply chain integration is needed. The research problem investigated is lack of supply chain integration and togetherness in IBS project delivery in Malaysia based on four objectives: (1) to investigate the SCM understanding and implementation in IBS projects; (2) to determine the challenges at each tier between players in order to facilitate supply chain integration among the players; (3) to identify means and dimension factors influencing successful integration at each tier between players; and (4) to develop a framework to enhance supply chain integration for successful IBS projects…